Risk Management Analysis in Digital Retail Companies - PAHLEVI , Davin Prayoga; KAMILA, Shafa; RASSI, Yehezkiel William; CAHYANI, Amelia Putri Indah; MAHARANI, Astriani Puspita; NURAYA, Ahmad Setiawan (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This study aims to describe the implementation of risk management in a digital retail company operating in the personal care and household products sector. The research focuses on risk identification, risk assessment, and mitigation strategies implemented by the company in facing the dynamics of the online retail business. The study used a qualitative-descriptive method through interviews with management, observation of operational processes, and review of internal documents. The analysis results indicate that the company faces various risks in human resources, operations, market, competition, and reputation. Assessment using a likelihood-impact matrix places most risks in the moderate category, requiring consistent control to prevent operational disruptions and reduced competitiveness. The company implemented a combination of strategies to strengthen standard operating procedures (SOPs), improve service quality, monitor the market, and fund internal and external risks to maintain business stability. These findings indicate that the implementation of risk management in the digital retail company has been quite successful but still requires ongoing evaluation to make the company more adaptive to changes in the digital business environment.